DESVELAR O URBANO: O Centro de Vitória-ES e o ensaio de uma experiência fenomenológica - Ramos, Vinicius Galvao (2020)
Western society has developed under the preponderance of rational and objective thinking since the Modern Age. Combined with the scientific and technological advances that have followed, objectivity has been applied predominantly in different areas of kno